2014
DOI: 10.1136/bmjspcare-2014-000724
|View full text |Cite
|
Sign up to set email alerts
|

The extent and cost of potentially avoidable admissions in hospital inpatients with palliative care needs: a cross-sectional study

Abstract: A significant proportion of patients with palliative care needs experience a potentially avoidable admission. Although these admissions are relatively short compared to those whose admissions are unavoidable, any hospital admission impacts on the experiences of patients and families and may contribute to unnecessary hospital expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Significant here is to discover, and act on patient and family preferences as opposed to using place of death as a key indicator of quality of end of life care [5,63]. Robinson et al [64] emphasise that end of life decision making can be a complex affair and it can be particularly difficult for patients to exercise autonomy in the face of an uncertain and limited future [64]. A co-design approach to policy development in palliative care is proposed to increase the match between services and patient needs and wishes [65].…”
Section: Discussionmentioning
confidence: 99%
“…Significant here is to discover, and act on patient and family preferences as opposed to using place of death as a key indicator of quality of end of life care [5,63]. Robinson et al [64] emphasise that end of life decision making can be a complex affair and it can be particularly difficult for patients to exercise autonomy in the face of an uncertain and limited future [64]. A co-design approach to policy development in palliative care is proposed to increase the match between services and patient needs and wishes [65].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed differing approaches have been adopted in the literature. For example, a study by Robinson et al [ 44 ] defined a potentially avoidable admission as one that occurred as a result of a predictable deterioration in the patient’s condition which could have been managed by community providers. In contrast, a study by Abel et al [ 45 ] considered a hospital admission to be avoidable if the patient could have stayed at home if services as described in England’s End of Life Care Strategy were available.…”
Section: Discussionmentioning
confidence: 99%
“…However, findings from a recent integrative review showed that, largely due to inadequacies in study design, what is known about patient and family experiences of palliative care in a hospital setting is limited to discrete aspects of care [ 47 ]. Moreover, a study published subsequent to the review found that patients with palliative care needs experience a range of benefits associated with being in hospital that extend beyond the treatment they receive and almost all participants expressed a preference to be in hospital during a period of acute illness [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors combined with limited training in palliative care may lead to some decisions to transfer patients who could have been successfully treated at home. One study found nearly a quarter of admissions of patients with palliative care needs were potentially avoidable 7. These admissions are also expensive: potentially avoidable admissions of people in the last year of life cost two hospitals in the North of England £5.9 million per year 8…”
Section: Discussionmentioning
confidence: 99%